Surgical Duration Impacts Venous Thromboembolism Risk in Microsurgical Breast Reconstruction - Qiu, Cecil S.; Jordan, Sumanas W.; Dorfman, Robert G.; Vu, Michael M.; Alghoul, Mohammed S.; Kim, John Y.S. (Journal of Reconstructive Microsurgery, 2018)
Background Increased surgical duration can impact patient outcomes and operative efficiency metrics. In particular, there are studies suggesting that increased surgical duration can increase the risk of venous thromboembolism (VTE). One of the longer duration plastic surgery procedures commonly performed is microsurgical breast reconstruction. With the widening indications for multiple and “stacked” free flaps to reconstruct breasts, we endeavored to assess (1) the relationship between duration of microsurgical breast reconstruction and VTE; and (2) determine if a threshold operative time exists that connotes VTE higher risk.Methods Patients from the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) between 2005 and 2014 who underwent microsurgical breast reconstruction were identified by Current Procedural Terminology code. Three models of multivariate logistic regression were used to characterize the adjusted risk for VTE by operative duration, bilaterality, the length of stay, and patient demographics.Results A total of 4,782 patients who underwent microsurgical breast reconstruction were identified. Overall VTE incidence was 1.13%. The mean operative duration was 8:31 hours:minutes (standard deviation: 2:59). Operative duration was statistically associated with VTE in continuous, quintile, and dichotomized risk models. Beyond an operative duration of 11 hours, adjusted VTE risk increases fourfold corresponding to a number needed to harm of 45.8.Conclusions Increasing surgical duration heightens the risk of VTE in microsurgical breast reconstruction. Increasing body mass index and age enhances this VTE risk. Moreover, limiting surgical duration to 11 hours or less can decrease VTE risk by fourfold vis-à-vis baseline.Level of Evidence Risk, II.
Keywords: surgical duration; venous thromboembolism; breast reconstruction